Serological and RT-PCR Surveillance for COVID-19 in an Asymptomatic US Army Trainee Population. (29th July 2021) - Hakre, Shilpa; Sanborn, Aaron D; Krauss, Stephen W; Burns, Jennifer L; Jackson, Kenya N; McCauley, Melanie D; Shepherd, Brittany L Ober; McHenry, Samantha; Stahlman, Shauna L; Bianchi, Elizabeth J; Freeman, Joanna; Ouellette, Jason; et al.
Abstract: Background: Significant variability exists in the application of infection control policy throughout the US Army initial entry training environment. To generate actionable information for the prevention of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)/coronavirus disease 2019 (COVID-19) transmission among new recruits, active enhanced surveillance was conducted for evidence of and exposure to SARS-CoV-2/COVID-19. Methods: We serially tested recruits with a reverse transcriptase polymerase chain reaction (RT-PCR) COVID-19 and/or total antibody to SARS-CoV-2 tests at days 0, 14, and week 10 upon arrival for basic combat training at a location in the Southern United States. Results: Among 1403 recruits who were enrolled over a 6-week period from August 25 through October 11, 2020, 84 recruits tested positive by RT-PCR, with more than half (55%, 46/84) testing positive at arrival and almost two-thirds (63%, 53/84) also testing seropositive at arrival. Similarly, among an overall 146 recruits who tested seropositive for SARS-CoV-2 during the period of observation, a majority (86%) tested seropositive at arrival; no hospitalizations were observed among seropositive recruits, and antibody response increased at week 10. Conclusions: These findings that suggest serological testing may complement current test-based measures and provide another tool to incorporate in COVID-19 mitigation measures among trainees in the US Army.